Comparação entre os métodos de extração quechers e miniluke modificados na extração de resíduos de pesticidas piretróides em tomate empregando GC×GC-μECD - Martel, Samile (2009)
In this study, two methods frequently used in the extraction of residues of pesticides in fruits and vegetables, the QuEChERS method and the mini-Luke method, were compared in order to optimize and validate these methods using quantification by GC×GC-μECD. This study was carried out for the pesticides bifenthrin, cyfluthrin, fenpropathrin, fenvalerate, esfenvalerate and permethrin cis and trans in tomato. In the QuEChERS method, 10 mL of acetonitrile containing 1% (v/v) of acetic acid was added to 10 g of sample. In the mini-Luke method, 30 mL of acetone, followed by 60 mL of a 1:1 (v/v) mixture of petroleum ether and dichloromethane were added to 10 g of sample. In the extraction method with acetonitrile, recoveries between 90.2 and 105.5% were obtained with RSD values lower than 8.7%, whereas, using the extraction method with acetone, the recoveries were between 86.2 and 110.8% with RSD values lower than 9.0%. In terms of limit of quantification (LOQ), the QuEChERS method presented values between 0.01 and 0.02 mg kg-1, considered more satisfactory than those obtained using the modified mini-Luke method (LOQ between 0.02 and 0.05 mg kg-1), where the value of LOQ found for cyfluthrin was above of the maximum limit of residues allowed by ANVISA, and therefore unsatisfactory. The r2 values from the analytical curves in the extract of the matrix were equal or higher than 0.9992 and 0.9955 for the modified QuEChERS method and the modified mini-Luke method, respectively, demonstrating that the modified QuEChERS method supplied more appropriate r2 values. Moreover, the QuEChERS method is a simpler procedure as it utilizes manual agitation and can be employed in any laboratory or in the field. Another important advantage of this method is the lower amount of solvent used. This study also showed that the GC×GC-μECD system using a modulator of double compressed air jet reduces costs and can be used in analyses of pyrethroid pesticides in tomato, with satisfactory values of LOD and LOQ, good precision and accuracy.